Fibrous and composite materials for civil engineering applications - Fangueiro, Raul Manuel Esteves de Sousa (Woodhead Publishing : Published in association with the Textile Institute, 2011)
The application of fibrous materials in civil engineering is an important and interesting development. Steel is one of the most popular composite materials used for structural applications, however many types of steel structures are subjected to corrosion damage. The use of fibrous structures including knitted, woven and braided fabrics are becoming recognised as an attractive reinforcement due to their fibre orientation, conformability and possibility of producing shaped reinforcements. This book will review these fibrous materials with regards to their role in structural reinforcement and also their non-structural applications, such as geotextiles and architectural membranes.
Keywords: Fibrous composites.; Civil engineering -- Materials.; elektronické knihy; electronic books